A Benchmark Study on the Properties of Unsubstituted and Some Substituted Polypyrroles - Ibeji, Collins U; Adejoro, Isaiah A; Adeleke, Babatunde B. (My University, 2015)
The geometric, thermodynamic, electronic and absorption properties of Pyrrole and some of its derivatives have been carried out using CCSD/6-311++G(d,p)/STO-3G, TD-DFT and DFT/B3LYP/6-31G(d) from monomer to five repeating units. Substitution by a methyl group at C3 and functional groups at C4 cause small changes in atomic distances. The estimated inter-ring bond length based on Badger's rule of 1.41 Å indicates that the average structure is about 30% quinoid. The geometries indicates that strong conjugate effects and effective aromatic structure are formed in the order Pyrrole>MPCam>MPC. The oligomers of simulated compounds have been extrapolated to polymer through second-degree polynomial-fit equation with r2 value ranging from 0.96-0.99. Calculated band gap of pyrrole, which is 2.9 eV, significantly correlates with the experimental value which ranges from 2.9-3.2 eV and this corresponds to π-π* transition energies. Natural bond orbitals of polypyrrole reveals that the wavefunctions contain dynamic correlations (single reference), closed shell character while substituted polypyrrole are multireference (static correlation), open shell character.
Keywords: Polypyrrole; Natural orbitals; Multireference; Band gap